2006
DOI: 10.1007/s10333-006-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrate removal using sugar-industry wastes

Abstract: Biological denitrification experiment was conducted using sugar-industry wastes, namely final molasses as a carbon source and bagasse charcoal pellets as supporting media for denitrifying bacteria. We employed an upflow fixed-bed reactor filled with the pellets and biofilm attached onto them. This was fed with potassium-nitrate and dilutemolasses solutions. Total nitrogen removals of more than 85% were achieved at influent carbon-nitrogen (C/N) ratios between 2 and 4, and hydraulic residence times of more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…bagasse, molasses) are also reported to be a good source of labile carbon (Frömmichen et al 2003;Ueda et al 2006). Unfortunately, sugarcane is not currently cultivated in the region; the only sugar mill in north Western Australia closed in 2007 (pers.…”
Section: Resultsmentioning
confidence: 97%
“…bagasse, molasses) are also reported to be a good source of labile carbon (Frömmichen et al 2003;Ueda et al 2006). Unfortunately, sugarcane is not currently cultivated in the region; the only sugar mill in north Western Australia closed in 2007 (pers.…”
Section: Resultsmentioning
confidence: 97%
“…The whole variety of substrates has been used in many studies mostly methanol [8,9], acetate [1,10], ethanol [11,12], and acetic acid [13,14]. Numerous different industrial waste products were tested, i.e., molasses [15,16], glycerol as a byproduct of biofuels production [17][18][19].…”
Section: Carbon Sourcementioning
confidence: 99%
“…Denitrification can be enhanced by adding carbonaceous materials to soil (Alexander 1977). Peat moss (Winkler 1991), molasses (Ueda et al 2006), and sawdust (Schipper et al 2000(Schipper et al , 2005 have been successfully used to reduce nitrate concentrations in septic systems. Jordan et al (1998) reported a ten-fold increase in denitrification in riparian forest soil amended with sucrose and Wang et al (2007) showed enhanced denitrification in lake sediment after adding sucrose.…”
Section: Secondary Treatment Of Windrowed Soilmentioning
confidence: 99%